Establishment of hotel business in the city of Zhytomyr: historical aspect - H.M. Tarasiuk; A.O. Chahaida; O.V. Milinchuk (Економіка, управління та адміністрування, 2020)
The modern policy for the development of the hotel business should be formed using the historical features of economic relations within the hospitality industry. The authors of the article have investigated the development of accommodation establishments in the city of Zhytomyr in the late XIX – early XX centuries within the European trends of that period. The historical stages of the city’s development are described according to the emphasis of socio-economic factors of the Zhytomyr central city status of Volyn province of the Russian Empire. The influence of economic and social factors on the growth of the level of service and the change in the number of hotel enterprises have been established. The history of hotel development in Kyiv, Lviv and Zhytomyr during the selected period is compared. The number of accommodation establishments in the city of Zhytomyr, their names and addresses according to the statistical data of 1907–1910 years are generalized. The role of restaurants and other food establishments near hotels is emphasized. The original advertisements of the local press of the period under study are illustrated by describing information on the opening of hotels, lists of services and other living conditions. In conclusion, the authors emphasize the lack of hotels of increased comfort in the early twentieth century due to the outdated material and technical base of buildings. The prospects of studying of the hotel business formation in the city of Zhytomyr during the Soviet period of the twentieth century are noted.